The impact and mechanism of the relaxation of fertility policy on income distribution: Evidence from China’s Selective Two Children Policy - Huang, Qian; Fang, Shoulin; Wang, Dongmei; Sun, Weiheng; Zhou, Youcheng; Lu, Feiling (Journal of Economic Analysis, 2023)
Numerous studies have explored the impact of family planning policies on income distribution, but the impact of policy relaxation remains largely unexplored. To address this gap, we investigate the effects of China’s selective two-child policy, which was implemented in 2013, using provincial panel data from 2011 to 2016. Specifically, we employ a generalized difference-in-differences model to empirically analyze the impact and mechanism of the policy relaxation on residents’ income distribution. Our findings are as follows. Firstly, the selective two-child policy has narrowed the income distribution gap. Secondly, male labor force participation, the urban-rural income gap, and disposable income serve as mechanisms through which the selective two-child policy affects income distribution. Thirdly, the robustness test confirms the robustness of our conclusions. Finally, we observe regional heterogeneity in the impact of the selective two-child policy on residents’ income distribution. Specifically, the policy has had significant effects in the western and northeastern regions, but not in other regions. Overall, our results shed light on the impact of childbearing policies on income distribution, providing important insights for optimizing China’s childbearing policies and promoting common prosperity.